(3GdoefJbi ef GdETGQIs - (3eLghds; (3oenZrdWGj Hf nbpdjL Hf YHO Gddg GdHcLQj GdeUQj GdMcQj GdMfaj, CHh YHO Gddg, YdGA GdOjf,J (B762 (3g` s
(3ChdgG (B:s
(3hdO HecI djdI GdEKfjf NdJG ef QHjY GdChd s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B275 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B313s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B159 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs